An analysis of spoken feedback on speech presentations / Wong Woei Ling - Wong , Woei Ling (2020)
Evaluative feedback is often observed in the context of language classroom and are often dialogic. A general rule of thumb is that evaluative feedback represents largely “post-observation evaluation” which relies on performance-based criteria. For non-dialogic evaluative feedback, it usually dwindles down to written form such as appraisal reports. The domain of non-dialogic spoken evaluative feedback is a domain which remains untapped due to restrictions to such interaction platform. This discourse study aims to describe different aspects of how non-dialogic spoken feedback is managed among trained evaluators within a specific linguistic context based on the Discourse Analysis Model that defines the "who", "what" and "how". The participants of this study are a specific group of individuals who act in giving motivating and evaluative post-observation spoken feedback after speeches have been presented. Data is collected in the form of video recordings, field notes and simple follow-up interviews. Data analysis has shown that the concluding elements of a successful spoken feedback lie in the identification of members in a discourse community and understanding of their roles. With this it is seen there are distinctive ways words are associated with spoken feedback and how feedback is socially constructed and within a specific discourse community. Findings of this study are significant as the specific study of this particular linguistic event is generic and transferable to other learning or language contexts which could benefit in assisting and encouraging an individual to move forward and strive for excellence in presentations.